FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KOSMETIK HALAL PADA MAHASISWA DI JAKARTA - Muthia Rizkitri Aulia; Handayani, Tati; Puspitasari, Lili (Journal of Sharia Economics, 2021)
This research is motivated by the increase in the halal cosmetic industry in Indonesia. Researchers have a goal to analyze several factors, namely, halal label, brand image, and price that affecting the interest of buying halal cosmetics to students in Jakarta. The method used is a quantitative approach with the number of samples processed as many as 130 respondents with the characteristics of Jakarta students who use make over cosmetics. The data collection technique was taken through a questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS) version 26 application. The data analysis technique was through validity testing, reliability testing, classical assumption testing, and multiple linear regression tests. Hypothesis test using F test, T test and determinant coefficient. The results showed that the variables of halal label, brand image, and price had a simultaneous effect on buying interest. Partially, the variables of halal label, brand image and price show a positive and significant influence on buying interest. With this, the researcher hopes to help the growth of local cosmetics so that there will be more and more good quality halal cosmetics.